Facilitating campus interactions – critical success factors according to university facility directors. Issue 9 (7th May 2021) - Jansz, Sascha Naomi; van Dijk, Terry; Mobach, Mark P.
Abstract : Purpose: The purpose of this paper is to investigate which critical success factors (CSFs) influence interaction on campuses as identified by the facility directors (FDs) of Dutch university campuses and to discuss how these compare with the literature. Design/methodology/approach: All 13 Dutch university campus FDs were interviewed (office and walking interview), focussing on CSFs relating to spaces and services that facilitate interaction. Open coding and thematic analysis resulted in empirically driven categories indicated by the respondents. Similarities and differences between the CSFs as previously identified in the literature are discussed. Findings: The following categories emerged: constraints, motivators, designing spaces, designing services, building community and creating coherence. The campus is seen as a system containing subsystems and is itself part of a wider system (environment), forming a layered structure. Constraints and motivators are part of the environment but cannot be separated from the other four categories, as they influence their applicability. Research limitations/implications: This study was limited to interviews with FDs and related staff. The richness of the findings shows that this was a relevant and efficient data collection strategy for the purpose of this study. Practical implications: By viewing the campus as an open system, this study puts the practical applicability of CSFs into perspective yet provides a clear overview of CSFs related to campus interaction that may be included in future campus design policies. Social implications: This (more) complete overview of CSFs identified in both literature and practice will help FDs, policymakers and campus designers to apply these CSFs in their campus designs. This improved campus design would increase the number of knowledge sharing interactions, contributing to innovation and valorisation. This could create a significant impact in all research fields, such as health, technology or well-being, benefitting society as a whole. Originality/value: This study provides a comprehensive overview and comparison of CSFs from both literature and practice, allowing more effective application of CSFs in campus design policies. A framework for future studies on CSFs for interaction on campuses is provided.